Potentiation of the activity of antibiotics against ATCC and MDR bacterial strains with (+)-α-pinene and (-)-borneol - Sampaio, Nadghia F. Leite (2022)
Ministério da Educação. Fundação Nacional de Pesquisa da Coréia. Governo coreano (MSIT).